2018
DOI: 10.1016/j.jpeds.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Race Effects of Inhaled Nitric Oxide in Preterm Infants: An Individual Participant Data Meta-Analysis

Abstract: iNO therapy should be considered for preterm African American infants at high risk for BPD. iNO to prevent BPD in African Americans may represent an example of a racially customized therapy for infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 33 publications
1
39
1
Order By: Relevance
“…(113)(114) A recent individual patient meta-analysis using data from a subset of trials suggested that inhaled nitric oxide may reduce BPD risk among black preterm infants. (115) This promising finding requires validation in future studies.…”
Section: Inhaled Nitric Oxidementioning
confidence: 95%
“…(113)(114) A recent individual patient meta-analysis using data from a subset of trials suggested that inhaled nitric oxide may reduce BPD risk among black preterm infants. (115) This promising finding requires validation in future studies.…”
Section: Inhaled Nitric Oxidementioning
confidence: 95%
“…Recent reports have investigated the relationship between race and BPD and respiratory outcomes following preterm birth. 7,8,[13][14][15][16][17] Implicit in many such investigations is the question as to whether genetic sequence differences between racial groups are responsible for differences in risk of diseases such as BPD.…”
Section: Geneticsmentioning
confidence: 99%
“…In post hoc analysis of the NO CLD study, there had been statistically significant interactions between age at study entry and ethnicity on treatment effect. 8,21 In that study, the benefit of survival without chronic lung disease was seen in the group treated at 7 to 14 days. Therefore, we performed secondary subgroup analyses to assess the effects of those variables on cardiopulmonary outcomes at school age.…”
Section: Discussionmentioning
confidence: 88%